Achieving Course Learning Outcomes through Efficient Planning of Teaching: A Case Study - Awwad Othman Abdelaziz Ahmed (European Scientific Journal, ESJ, 2023)
Teachers, in general, would face great difficulty in being able to conduct a lesson in such a way, as he/she would not be in a good position to deal with some of the language problems that may arise from unplanned classes; therefore, may lose the their normal running and administration. Thus, the investigator tried to find out to what extent EFL teachers plan their lectures efficiently and successfully. This was carried out by administering a questionnaire handed out to (13) males and (13) females teaching staff at the English Language Center (ELC) in Taif University, KSA. The results of a (T) test performed at the (0.05) significance level suggest that class or lesson planning is crucial for effectual language teaching and learning. It ascertains success for the teacher as well as the learner. It is essential for teachers to draw up a mechanism for making decisions about the principle of their lessons, which enables in achieving learning outcomes. Teachers need to plan for the situations that he or she will teach, and the techniques, methods and procedures he or she will use.